Beat your parodies into swords, and your parodied books into spears: A new paradigm for parody in the hebrew bible - Kynes, W (2011)
While previous works on parody in the Hebrew Bible have addressed the literary technique ad hoc in the service of the interpretation of specific texts, this article approaches the topic more broadly, attempting to understand the nature of the technique itself. Drawing on literary criticism, particularly the work of Linda Hutcheon, the commonly accepted definition of parody as a text which "ridicules" its "target" is questioned, and a broader definition of parody as "antithetical allusion," in which the earlier text may act as a "weapon" instead of a "target," and subversion and humor are only secondary features, is presented. This redefinition of the term grounds a new paradigm for parody that divides parody into four types: ridiculing, rejecting, respecting, and reaffirming. This paradigm is then applied to a series of exemplary parodies in the Hebrew Bible (Song 7:1-10, Psalm 29, Jonah, Job 7:17-18, Joel 4:10) that demonstrate the versatility of parody and the necessity of reading parodies in their wider context to determine their meaning. © 2011 Koninklijke Brill NV, Leiden.